Contested statehood : Kosovo's struggle for independence - Weller, M. (Marc) (Oxford : Oxford University Press, 2009)
This is a critical analysis of the international attempts to settle the Kosovo crisis, written from first hand insights of the settlement attempts. It covers several strands of analysis including the tension between state sovereignty and humanitarian concerns.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Kosovo War, 1998-1999 -- Law and legislation; Kosovo (Republic) -- International status; Kosovo (Republic) -- History -- Autonomy and independence movements